2008
DOI: 10.1002/elps.200700806
|View full text |Cite
|
Sign up to set email alerts
|

Use of quasi‐isoelectric buffers as anolyte and catholyte to improve capillary isoelectric focusing performances

Abstract: The use of quasi-isoelectric anolytes and catholytes has been investigated to improve CIEF performances. Narrow pH cuts of carrier ampholytes (NC) have been compared to more conventional couples of anolytes/catholytes (phosphoric acid/sodium hydroxide and glutamic acid/lysine). First, a CIEF setup that consists in a bare silica capillary and 70:30 water/glycerol separation medium has been used. The experiments have shown that when using NC instead of more classical anolytes and catholytes, an increase in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Fig. illustrates that pH 3–10 CAs were compressed near the cathode, a common phenomenon reported previously . In a large slab gel with small reservoirs that allowed electrolytes to diffuse into the gel, the pH gradient was observed to compress due to differing anion and cation migration rates within the gel .…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Fig. illustrates that pH 3–10 CAs were compressed near the cathode, a common phenomenon reported previously . In a large slab gel with small reservoirs that allowed electrolytes to diffuse into the gel, the pH gradient was observed to compress due to differing anion and cation migration rates within the gel .…”
Section: Resultssupporting
confidence: 72%
“…Ideally, commercial carrier ampholytes should generate a linear pH gradient that spans the anode to cathode gel length of 300 m. Fig. 3 illustrates that pH 3-10 CAs were compressed near the cathode, a common phenomenon reported previously [6,44,[50][51][52][53][54]. In a large slab gel with small reservoirs that allowed electrolytes to diffuse into the gel, the pH gradient was observed to compress due to differing anion and cation migration rates within the gel [55].…”
Section: Ph Calibration and Ph Gradient Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopez‐Soto‐Yarritu et al enhanced the resolution of sample components by titrating the sodium hydroxide catholyte with phosphoric acid. In the presence of EOF, Poitevin et al observed altered resolution by using quasi‐isoelectric amphoteric anolytes and catholytes, i.e., narrow pH cuts of carrier ampholytes or amino acids. Cui et al modified the pH gradient with applying narrow range ampholytes as electrolytes in multistage on‐chip IEF experiments in a polymeric (PDMS) microchip, whereby segments of the samples separated in the first stage with broad‐range ampholytes were refocused within narrower pH ranges in order to achieve higher resolving power.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been adapted to capillaries (cIEF) [40] and microdevices [1]. Capillary IEF designs from the last 2 years utilized capillaries in the tens of centimeters range [41,42], falling outside the scope of this review. Although there are several applications of IEF in microdevices in the last 2 years, these designs still use channels whose lengths are in the centimeter range [43][44][45][46][47][48].…”
Section: Iefmentioning
confidence: 99%